2013
DOI: 10.1007/s11032-013-9884-2
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic acid and the herbicide safener cyprosulfamide cooperatively enhance abiotic stress tolerance in rice

Abstract: Plants adapt to abiotic stress by undergoing diverse biochemical and physiological changes that involve hormone-dependent signaling pathways. The effects of plant hormones can be mimicked by exogenous chemical regulators such as herbicide safeners, which not only enhance stress tolerance but also confer hormetic benefits such as increased vigor and yield. In this study, rice plants growing in normal and saline soils were exposed to abscisic acid (ABA), the safener cyprosulfamide or both compounds together. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 61 publications
0
18
0
Order By: Relevance
“…For example, safeners are agrochemicals that decrease herbicide injury in cereal crops without reducing efficacy on target weeds, and function by increasing the expression of defence genes and enzymes involved in herbicide detoxification mechanisms (Riechers et al., 2010). Further, safener treatments are associated with detoxifying cytotoxins and stress‐induced reactive oxygen species (ROS), and as a result lead to increased protection from herbicides, pollutants, and abiotic stresses (Dashevskaya et al., 2013; DeRidder et al., 2002; Jablonkai, 2013; Panfili et al., 2017; Panfili et al., 2019; Riechers & Green, 2017; Riechers et al., 2010; Taylor et al., 2013; Ye et al., 2019). Among the many approaches used to enhance abiotic stress tolerance in plants, exogenous application of agrochemicals such as safeners is considered a new strategy (Abu‐Qare & Duncan, 2002; Bianchi et al., 2020; Dashevskaya et al., 2013; Taylor et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For example, safeners are agrochemicals that decrease herbicide injury in cereal crops without reducing efficacy on target weeds, and function by increasing the expression of defence genes and enzymes involved in herbicide detoxification mechanisms (Riechers et al., 2010). Further, safener treatments are associated with detoxifying cytotoxins and stress‐induced reactive oxygen species (ROS), and as a result lead to increased protection from herbicides, pollutants, and abiotic stresses (Dashevskaya et al., 2013; DeRidder et al., 2002; Jablonkai, 2013; Panfili et al., 2017; Panfili et al., 2019; Riechers & Green, 2017; Riechers et al., 2010; Taylor et al., 2013; Ye et al., 2019). Among the many approaches used to enhance abiotic stress tolerance in plants, exogenous application of agrochemicals such as safeners is considered a new strategy (Abu‐Qare & Duncan, 2002; Bianchi et al., 2020; Dashevskaya et al., 2013; Taylor et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was found that cyprosulfamide, alone or with abscisic acid (ABA), protected plants (e.g. rice) from salinity stress and induced vigorous growth, including the formation of new tillers and early flowering …”
Section: Safeners For Weed Controlmentioning
confidence: 99%
“…rice) from salinity stress and induced vigorous growth, including the formation of new tillers and early flowering. 88 wileyonlinelibrary.com/journal/ps In spite of enormous screening efforts by many researchoriented companies, safeners for dicotyledenous crops such as soybean, canola and sugar beet could not be identified. It was found that a broad-spectrum, one-application weed control was only efficient by using mixtures.…”
Section: Safeners For Weed Controlmentioning
confidence: 99%
“…Interestingly, the combination of ABA and cyprosulfamide prolonged the expression of stress-responsive genes beyond the stress period, and facilitated the plants in maintaining their improved growth. Proteomic analyses revealed that several photosynthetic proteins, including photosystem b P protein (PsbP) and PsbO, were either repressed or induced with the exogenous application of ABA in combination with cyprosulfamide, further indicating a strong interaction between ABA signaling and the regulation of the photosynthetic apparatus under environmental stress [ 131 ]. It is apparent with the findings discussed above that ABA signal perception and transduction are closely associated with redox signaling and other signaling pathways.…”
Section: Psii Damage and Role Of Hormonesmentioning
confidence: 99%